Intestinal malrotation with midgut volvulus: associations and role of elective surgery in adults - Mohan, Aishwarya; Ansari, Waqar A.; Gada, Parth B.; Dandge, Snehal M.; Nagwani, Pooja D. (International Surgery Journal, 2022)
Intestinal malrotation, a congenital anomaly of rotation of midgut, with paediatric dominant presentation is increasingly being observed in adult population. Here, the severity of presentation ranges from asymptomatic to life threatening midgut volvulus. Presentation with midgut volvulus, managed by an emergency surgery with definitive Ladd’s procedure is the current standard. Presently, there is no data to support elective repair in stable patients with chronic midgut volvulus. Management of asymptomatic adult with malrotation is also a topic of controversy with no recommended guidelines. We herein, present two cases of malrotation with midgut volvulus with initial conservative management followed by elective Ladd’s procedure. Rare associations like nutcracker phenomenon and pancreatitis were also observed in one of our patients. Our study aims to correlate our findings with the published literature, to understand these associations better and to review the need for an emergent operation for chronic midgut volvulus.